Peran Edukasi Gizi dan Suplementasi Makanan Tambahan dalam Mengurangi Risiko Stunting pada Balita - Lede, Yohanes Umbu; Solo, Marinaus; Jati, Brigita A. Lawa (Varied Knowledge Journal, 2024)
Stunting in children under five is one of the chronic nutritional problems that remains a major challenge in Indonesia. This condition not only affects children's physical growth, but also impacts cognitive ability, future economic productivity and the overall quality of human resources. This study aims to analyze the role of nutrition education and supplementary food supplementation in reducing the risk of stunting in children under five. The study used a cross-sectional design with a sample of 30 children under five selected by random sampling. Data were collected through a questionnaire that included acceptance of nutrition education, use of additional food supplementation, and stunting status in toddlers. The results showed that 60% of children under five received nutrition education, and 66.7% received additional food supplementation. The prevalence of stunting among children under five who received nutrition education and supplementation was only 11.1%, while among children under five who did not receive either, the prevalence reached 50%. This finding suggests that proper nutrition education and regular supplementation play a significant role in preventing stunting. This study emphasizes the importance of nutrition education interventions and supplementary food supplementation as a strategy to reduce stunting among under-fives.